Satisfação dos usuários de um Centro de Atenção Psicossocial relacionada à acessibilidade na assistência à saúde - Moreira , Ana Caroline Gonçalves Cavalcante (2016)
There are international health organizations recommendation for the evaluation of mental health services in the world especially by the actors involved in assistance, workers, users and their families. In Brazil there are several investments that aim to meet the psychosocial model of attention, from the guidelines of the national policy on mental health. This study aimed to assess the satisfaction of users and family Psychosocial Attention Center (CAPS-Brazilian acronym) with respect to accessibility in health care. This is a descriptive-exploratory research qualitative in nature, which was attended by 35 users and 11 relatives of a “CAPS” of the municipality of Goiania-GO. The data were obtained through documentary research participant observation, field journal and in addition to group interviews. Were subjected to content analysis with the aid of software ATLAS.ti and organized into four categories: Location and structure of the service the host team and aid received competence and understanding of the team about the problem of user, psychosocial model and elements involved. The results showed that varies the satisfaction of participants regarding the location of the service to prepare the team to offer qualified and guidance listening to space for exchange of knowledge and experiences inter alia. However dissatisfaction is common especially in relation to the physical structure of the “CAPS” availability of materials and equipment for performing groups and workshops as well to attend the clinical intercurrences/psychiatric hospital service apart from the lack of urgency and emergency support. The host was discussed among the timely production of health practices in which they stressed the listening and understanding the team about the problem of the users as well and also the reduction of symptoms related to mental illness; changes in family dynamics and reducing the number of hospitalizations from the treatment received in the service. We must therefore empower customers, targeting their autonomy, even in the face of limitations and other adversities. It reflects also the need to encourage the evaluative processes as fundamental practice in planning and management of services to better meet the needs and demands of users of mental health services.